The Effect of Library Utilization and Interest in Reading English Text Book With Reading Comprehension Ability on Students of SMK Kesehatan Nafsiah Stabat - Rudi Purwana; Mariana (International Journal of Cultural and Social Science, 2021)
Libraries can play an active role in finding, exploring, fostering, and developing as well as channeling hobbies / hobbies, interests, and talents possessed by the community through various activities that can be organized by the library. To improve reading comprehension ability, it is influenced by students' reading interest. Interest has a great influence on learning, because if the subject matter being studied is not in accordance with the interests of students, students will not learn as well as possible because there is no attraction for them. The purpose of this study was to determine the effect of library utilization and interest in reading English text books with reading comprehension ability in students of SMK Kesehatan Nafsiah Stabat. This type of research is explanatory research. According to Singarimbun and Efendi Explanatory research is a hypothesis testing research. This research is intended to explain the causal relationship between the research variables and to test the formulated hypothesis. The population in this study were 89 people and the total sample was 89 people. From the results of the F test or simultaneous test (ANOVA) it was found that the calculated F result was 16,532 with a significance of 0.000a. . At = 0.05 with: df1= k-1 = 3-1 = 2, df2 = N-k = 89-3= 86 above in Ftable = (3,11). It turns out that Fcount (16.532) > Ftable (3.11), this means that Ho is rejected. Ha is accepted. The conclusion of the study is that there is an effect of Library Utilization and Interest in Reading English Text Books with Reading Comprehension Ability in English Subjects for class X students. It is recommended that students of SMK Kesehatan Nafsiah Stabat pay more attention to and utilize Library Facilities and Infrastructure in order to achieve maximum learning objectives.